N-Terminal Truncation Of Pha Synthase (Phacbp-M-Cpf4) As A Strategy For Improved Polyhydroxyalkanoate Properties By Cupriavidus Necator - Neoh, Soon Zher (2025)
Polyhydroxyalkanoate (pha) is a type of bio-based and biodegradable polyester, synthesized by most bacteria and archaea under excess carbon and limited nutrient conditions. Among the types of pha, poly[(r)-3-hydroxybutyrate-co-(r)-3-hydroxyhexanoate] [p(3hb-co-3hhx)] is reported to have a close resemblance to the commercial polypropylene (pp) and low-density polyethylene (ldpe). Pha synthase (phac) is the most important enzyme in pha biosynthesis as it determines the properties of the pha produced. The structure of a phac consists of an n- and c-terminal. To date, there are not many productive phacs reported for the production of p(3hb-co-3hhx). Previous studies have shown that phac isolated from mangrove soil metagenome, phacbp-m-cpf4 is an efficient phac for p(3hb-co-3hhx) production and n-terminal influences substrate specificity and dimerization for the phac to function, granule morphology and molecular weight of pha produced. The full-length or nearly full-length structure of phacbp-m-cpf4 was successfully predicted using the alphafold software and psipred server. The n-terminal of phacbp-m-cpf4 was truncated based on its predicted structure giving rise to 4 n-terminal truncated mutants, phacbp-m-cpf4 g8, a27, t74, and d104 and cloned into cupriavidus necator phb−4.